An analysis of interest in students learning of physical chemistry experiment using Scientific approach - Widinda Normalia Arlianty (Universitas Sebelas Maret, 2017)
This study was aimed to analyze interest in student learning of physical chemistry experiment on Chemistry Education students, Islamic University of Indonesia. The research was quantitative. The samples of this research were 2nd-semester student academic year 2015. The data learning interest of students were collected by questionnaire and documentation of seven title experimental. Learning interest consisted of three indicators, concluded feeling good, attention and activity in the learning process. The results of this research showed that score mean of feeling good indicator was 25,9; score mean of attention indicator 17,8, and score mean of activity indicator 8,41. Score Mean students for the questionnaire interest in student learning was 51,83 and this data was categorized as “good”.